Characterizing the Richness of Maternal Input for Word Learning in Neurogenetic Disorders - Mattie, Laura J.; Hadley, Pamela A. (Seminars in Speech and Language, 2021)
Promoting language abilities, including early word learning, in children with neurogenetic disorders with associated language disorders, such as Down syndrome (DS) and fragile X syndrome (FXS), is a main concern for caregivers and clinicians. For typically developing children, the quality and quantity of maternal language input and maternal gesture use contributes to child word learning, and a similar relation is likely present in DS and FXS. However, few studies have examined the combined effect of maternal language input and maternal gesture use on child word learning. We present a multidimensional approach for coding word-referent transparency in naturally occurring input to children with neurogenetic disorders. We conceptualize high-quality input from a multidimensional perspective, considering features from linguistic, interactive, and conceptual dimensions simultaneously. Using case examples, we highlight how infrequent the moments of word-referent transparency are for three toddlers with DS during play with their mothers. We discuss the implications of this multidimensional framework for children with DS and FXS, including the clinical application of our approach to promote early word learning for these children.
Keywords: Down syndrome; fragile X syndrome; maternal language input; maternal gesture use; word learning